Studies of dermatoglyphics in twins - Dobrzańska, Alina; Grzeszyk, Czesław (Anthropological Review, 1974)
Five hundred dermatoglyphes of fingers and hundred dermatoglyphes of the palm were studied in 25 pairs of twins. In this material 10 MZ and 15 DZ twins were previousiy examined from the anthropological and psychological point of view at the Department of Child Development. Nine dermatoglyphics were analysed as follows: 1) the patterns of finger tips; 2) the patterns of base phalanx: 3) the patterns of medial phalanx: 4) ridge design on the thenar: 5) ridge design on the hypothenar: 6) the value of a t d angle; 7) the position of a t d angle; 8) ridge — count between a — b; 9) the design's direction on fingertips (ulnar, radial, and symmotrical). In the estimation of MZ and DZ. the index of similaritics of dermatoglyphic patterns were used. In the numerator of this index there are the number of the concordant features and in the denominator the sum of all analysed features. The LS.D.P. was counted for particular pairs of MZ and DZ twins and for the children of the control group of non-relatives. The index of similarities established on the base of 9 dermatoglyphic features for MZ twins is from 75 to 93, average 87,07, for DZ twins from 50 to 72,95, average 62,77; and for control group of children it oscillates from 18,75 to 72,92, average 54,48. In the differentiation of MZ and DZ twins, the most indicative were those features of dermatoglyphes as: the patterns of fingertips and the value of the a t d angle.